Field trip to Integrative Pharmacogenomics Institute (iPROMISE) - UiTM, Faculty of Law (Faculty of Law, 2019)
The class of LAW587 (2019) went on field trip to the exceptional Integrative Pharmacogenomics Institute (iPROMISE) at UiTM Puncak Alam Campus. This is an educational program related to the subject of LAW587 (Intellectual Property law II) where part of the syllabus deals with patents and genetic resources and how it affects patent law in Malaysia. It was held on the Tuesday, 15th of October 2019, from 10 am to 12.30 pm with the involvement of 23 students and the subject lecturer, Puan Farizah Mohamed Isa. This program is intended to provide practical exposure to students that are taking this subject. Students were able to get information on technologies related to human DNA In addition, students will also use the knowledge that they will be gaining to complete the assignments throughout the semester as a reference. UiTMLaw thanks the Director of iPROMISE, Professor Dato' Dr. Mohd Zaki Salleh and the Deputy Director, Professor Dr. Teh Lay Kek for graciously hosting the programme. Professor Dr Teh Lay Kek gave a lecture on the introduction of human DNA. Students also took the opportunity to ask questions and discussed how Personal Genome Sequencing is related to Patent law in Malaysia. Students were also given the opportunity to watch the process of collecting human DNA for the process of Personal Genome Sequencing. All in all, the students unanimously agreed that they had a very informative and interesting time throughout the programme and the knowledge they gained will be very helpful for them in the years to come.